2002
DOI: 10.1292/jvms.64.933
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Hip Joint Congruity after Triple Pelvic Osteotomy in the Dog with Hip Dysplasia.

Abstract: ABSTRACT. Changes in hip joint congruity was evaluated in dogs with hip dysplasia before and after triple pelvic osteotomy by computed tomography examination in the standing position. Lateral center edge angle significantly increased, and center distance (CD) significantly decreased after surgery compared to the values before surgery, respectively. There was an inverse proportion between the postoperative period and the change in the ratio of CD. These results suggested that joint laxity was improved with time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…Hara et al 15 reported an incidence of 25% females 75% in the male dogs. Bakır 16 have been reported that hip dysplasi were 29.56% in males, 39.06% females in dogs.…”
Section: Discussionmentioning
confidence: 97%
“…Hara et al 15 reported an incidence of 25% females 75% in the male dogs. Bakır 16 have been reported that hip dysplasi were 29.56% in males, 39.06% females in dogs.…”
Section: Discussionmentioning
confidence: 97%
“…Computed tomography scans were performed in the two positions according to the procedures previously reported [4,6,11]. The dogs, under isoflurane anesthesia, were positioned on a platform in ventral recumbency with the vertebrae parallel to the platform.…”
mentioning
confidence: 99%
“…Two lines were then drawn perpendicular to this line: one at the lateral aspect of the dorsal acetabular rim and one at the medial aspect of the femoral head [4,8,11]. The lateral center edge angle was defined as the angle determined by the dorsal edge of the acetabulum, the center of the femoral head, and a horizontal line on CT images [1,6]. The center distance (CD) index was calculated as the distance between the center of the femoral head and the center of the acetabulum, divided by the measured radius of the femoral head (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations